Snowdrift - Tursten, Helene, 1954- (Tursten, Helene, 1954- Embla Nyström investigations, 2020)
"One winter night, 28-year-old Detective Inspector Embla Nyström receives a phone call that sends her reeling. It's been fifteen years since Embla's best friend disappeared from a nightclub in Gothenburg, but Embla recognizes her voice immediately, though the call quickly disconnects. Lollo is still alive. But before Embla can dive into the case, she gets another phone call, this time from her cousin. A man has been found shot to death in one of the guest houses he and his wife manage in rural Sweden. When Embla arrives on the scene, she receives another shock. The dead man is Milo Stavic, a well-known gang member and one of the men she saw with Lollo the night she disappeared. And, as Embla soon learns, the same night that Milo was shot in bed, his brother Luca was also killed. Why, after all these years, is someone targeting the Stavic brothers, and where is the third brother? With help from a handsome local detective and his poorly trained Belgian shepherd, Embla launches an investigation into the three Stavic brothers, hoping it will bring her closer to finally finding Lollo and putting an end to her terrible nightmares"--